Preferential Cochleotoxicity of Cisplatin - Prayuenyong, Pattarawadee; Baguley, David M.; Kros, Corné J.; Steyger, Peter S. (Frontiers in Neuroscience, 2021)
Cisplatin-induced ototoxicity in humans is more predominant in the cochlea than in the vestibule. Neither definite nor substantial vestibular dysfunction after cisplatin treatment has been consistently reported in the current literature. Inner ear hair cells seem to have intrinsic characteristics that make them susceptible to direct exposure to cisplatin. The existing literature suggests however that cisplatin might have different patterns of drug trafficking across the blood-labyrinth-barrier, or different degrees of cisplatin uptake to the hair cells in the cochlear and vestibular compartments. This review proposes an explanation for the preferential cochleotoxicity of cisplatin based on current evidence as well as the anatomy and physiology of the inner ear. The endocochlear potential, generated by the stria vascularis, acting as the driving force for hair cell mechanoelectrical transduction might also augment cisplatin entry into cochlear hair cells. Better understanding of the stria vascularis might shed new light on cochleotoxic mechanisms and inform the development of otoprotective interventions to moderate cisplatin associated ototoxicity.